-3 Step-by-step explanation: 4r-3=3(3r+4) 4r-3=9r+12 -3=9r-4r+12 -3=5r+12 -3-12=5r -15=5r -15/5=5r/5 -3=r

r=-3 Step-by-step explanation: Step 1: Simplify both sides of the equation.

4r−3=3(3r+4)

4r+−3=(3)(3r)+(3)(4)(Distribute)

4r+−3=9r+12

4r−3=9r+12

Step 2: Subtract 9r from both sides.

4r−3−9r=9r+12−9r

−5r−3=12

Step 3: Add 3 to both sides.

−5r−3+3=12+3

−5r=15

Step 4: Divide both sides by -5.

−5r

−5

=

15

−5

Mark me brainliest if this helped

Step-by-step explanation: r=-3 Isolate the variable by dividing each side by factors that don’t contain the variable.

r = -3 Step-by-step explanation: 4r – 3=3( 3r + 4 ) 4r – 3 = 9r + 12 -12 -3 = 9r – 4r 5r = -15 r = -3 Can I get brainliest

Latest posts by Answer Prime (see all)

- How to Get Bad Credit Online Loans for Fast Emergency Funding - February 1, 2023
- What does an audio engineer do in post-production? - February 1, 2023
- Men and Women of the Civil War Crossword? - February 1, 2023